2019
DOI: 10.1159/000504689
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Simple, Complex, and Clonal Chromosome Translocations Induced by Internal Radioiodine Exposure: A Cytogenetic Follow-Up Case Study after 25 Years

Abstract: Here, we report the findings of a 25-year cytogenetic follow-up study on a male patient who received 2 rounds of radioiodine treatment within a span of 26 months (1.78 GBq in 1992 and 14.5 GBq in 1994). The patient was 34 years old with a body mass index of 25 at the time of the first radioiodine treatment. Multicolor FISH and multicolor banding (mBAND) techniques performed on the patient detected inter- and intrachromosomal exchanges. Although the frequency of chromosome translocations remained essentially th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 42 publications
9
12
2
Order By: Relevance
“…In the first examined sample (day 1959), among 11.8 CA/100 cells, 61.6% were translocations ( Table 1 ), attributable to the previous exposures of PBL and bone marrow. The observed pattern was close to that described in [ 22 ], a 25-year follow-up study of a DTC patient, which reported 66 translocations in 669 cells, whereas we observed 54 translocations in 526 cells. No clonal aberrations, which reflect early damage to bone marrow stem cells and are defined as at least three cells with identical translocations, were found [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the first examined sample (day 1959), among 11.8 CA/100 cells, 61.6% were translocations ( Table 1 ), attributable to the previous exposures of PBL and bone marrow. The observed pattern was close to that described in [ 22 ], a 25-year follow-up study of a DTC patient, which reported 66 translocations in 669 cells, whereas we observed 54 translocations in 526 cells. No clonal aberrations, which reflect early damage to bone marrow stem cells and are defined as at least three cells with identical translocations, were found [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…The baseline frequency of dicentric chromosomes in the general population is estimated to be 0.001/cell (one dicentric chromosome in 1000 metaphase cells [57]). The frequency of dicentric chromosomes detected in the radioiodine patient was 0.02/cell and 0.006/cell, respectively, after 21 and 25 years of the second RIT [53,56]. Although the frequency of dicentric chromosomes declined over the years, it was still sixfold higher than the baseline frequency reported for the normal population.…”
Section: Internal Radioiodine Exposurementioning
confidence: 66%
“…Cancer patients undergoing therapy with radioiodine ( 131 I) provide unique opportunities to investigate the acute and chronic effects of radiation administered under carefully controlled conditions, allowing prospective follow-up studies for extended periods. In our earlier studies, the cytogenetic effects were demonstrated in the peripheral blood lymphocytes of a 34 year old patient [53][54][55][56] who received two rounds of ablative radioactive 131 I therapy (RIT) in 1992 (1.78 GBq; 48 mCi) and 1994 (14.5 GBq; 392 mCi), respectively, after a total thyroidectomy for his papillary thyroid adenocarcinoma. Prior to radioiodine therapy, the patient did not have any occupational or medical exposure to radiation.…”
Section: Internal Radioiodine Exposurementioning
confidence: 99%
“…Fluorescence in situ hybridization (FISH)-based translocation assay is a representative methodology to assess stable chromosomal aberrations [32], which could help to study further the impact of their occupational radiation exposure on stable chromosomal damages. Specifically, the 24-multicolor FISH technique would allow evaluating complex chromosome exchanges induced by high LET radiation and thereby find the contribution of neutron exposure to the chromosomal damages of our subjects [33][34][35] Another limitations to this study includes the low number of multiaberrant cells, the inexact criteria for multi-aberrant cells, and the fact that insignificant amounts of neutron exposure contribute to all external effective doses.…”
Section: Discussionmentioning
confidence: 99%